Impaired tryptophan metabolism in the gastrointestinal tract of patients with critical coronavirus disease 2019 - Yokoyama, Yoshihiro; Ichiki, Tomoko; Yamakawa, Tsukasa; Tsuji, Yoshihisa; Kuronuma, Koji; Takahashi, Satoshi; Narimatsu, Eichi; Nakase, Hiroshi (Frontiers in Medicine, 2022)
【Introduction】 Coronavirus disease 2019 (COVID-19) is still causing a global pandemic. But the mechanism of COVID-19 severity is not well elucidated. 【Materials and Methods】 We conducted two single-center observational studies of patients with COVID-19. In the first study, the enrolled patients were distinguished based on critical vs. noncritical COVID-19. We collected blood samples from the patients at admission to measure markers related to inflammation and thrombosis and stool samples to analyze the fecal microbiome, metabolome, and calprotectin level. In the second study, we collected ileum and colon tissue samples from patients with critical COVID-19 who required colonoscopy due to severe gastrointestinal symptoms and analyzed mucosal gene expression. 【Results】 A total of 19 blood samples and 10 stool samples were collected. Interleukin (IL)-6 was the only serum inflammatory marker with significantly higher levels in the critical group than in the noncritical group. The fecal calprotectin level in the critical group was significantly higher than that in the noncritical group (P=0.03), regardless of the presence of gastrointestinal symptoms. Stool metabolomic analysis showed that the level of indole-3-propionic acid, a ligand for aryl hydrocarbon receptor (AhR), was markedly decreased in the critical group compared to that in the noncritical group (P=0.01). The expression of genes involved in tryptophan metabolism, including ACE2, AHR, CARD9, and IL22, was downregulated in the ileum of critical COVID-19 patients who required a colonoscopy. 【Discussion】 Critical COVID-19 patients have gastrointestinal inflammation potentially caused by impaired tryptophan metabolism in the small intestine due to decreased expression of genes involved in tryptophan metabolism.